Advanced Nursing Experience Is Beneficial for Lowering the Peritonitis Rate in Patients on Peritoneal Dialysis - Yang, Zhikai (Multimed Inc, 2012)
♦ Objectives: We explored the relationship between the experience level of nurses and the peritonitis risk in peritoneal dialysis (PD) patients. ♦ Methods: Our observational cohort study followed 305 incident PD patients until a first episode of peritonitis, death, or censoring. Patients were divided into 3 groups according to the work experience in general medicine of their nurses—that is, least experience (<10 years), moderate experience (10 to <15 years), and advanced experience (≥15 years). Demographic characteristics, baseline biochemistry, and residual renal function were also recorded. Multivariate Cox regression was used to analyze the association of risks for all-cause and gram-positive peritonitis with patient training provided by nurses at different experience levels. ♦ Results: Of the 305 patients, 91 were trained at the initiation of PD by nurses with advanced experience, 100 by nurses with moderate experience, and 114 by nurses with the least experience. Demographic and clinical variables did not vary significantly between the groups. During 13 582 patient–months of follow-up, 129 first episodes of peritonitis were observed, with 48 episodes being attributed to gram-positive organisms. Kaplan–Meier analysis showed that training by nurses with advanced experience predicted the longest period free of first-episode gram-positive peritonitis. After adjustment for some recognized confounders, the advanced experience group was still associated with the lowest risk for first-episode gram-positive peritonitis. The level of nursing experience was not significantly correlated with all-cause peritonitis risk. ♦ Conclusions: The experience in general medicine of nurses might help to lower the risk of gram-positive peritonitis among PD patients. These data are the first to indicate that nursing experience in areas other than PD practice can be vital in the training of PD patients.